THE EFFECT OF CURRENT RATIO (CR) AND DEBT TO ASSET RATIO (DAR) ON PROFIT GROWTH AT PT. DHARMA SATYA NUSANTARA TBK - Muhammada Arfah (Pustaka Digital Indonesia, 2026)
This study aims to examine the influence of Human Resource Management (HRM) practices on organizational performance through a systematic literature review across various industrial sectors. In the context of globalization and rapid digital transformation, organizations are required to optimize human capital as a strategic resource to achieve sustainable performance. This research adopts the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to analyze approximately 50 peer-reviewed articles published between 2021 and 2025 from reputable databases such as Scopus, Web of Science, ScienceDirect, and SpringerLink. The findings reveal that core HRM practices—recruitment and selection, training and development, performance appraisal, compensation, and employee engagement—have a significant positive impact on both financial and non-financial organizational performance. The study also identifies innovation, knowledge management, and employee engagement as key mediating variables that strengthen the relationship between HRM practices and performance outcomes. Additionally, leadership style and organizational culture are found to act as critical moderating factors influencing the effectiveness of HRM implementation. Furthermore, the results highlight emerging trends in digital HRM and sustainable HRM, which play a crucial role in enhancing organizational adaptability, efficiency, and long-term sustainability. The study concludes that an integrated and context-specific HRM approach is essential for maximizing organizational performance across different industrial sectors. These findings provide valuable theoretical and practical implications for managers, policymakers, and researchers in developing effective HR strategies in a dynamic business environment.